Dialectics and the Sublime in Evelyn Underhill's Mysticism: The Nature and Development of Spiritual Consciousness (KEMANUSIAAN The Asian Journal of Humanities, 2016)
Dialectics and the Sublime in Evelyn Underhill's Mysticism: The Nature and Development of Spiritual Consciousness